Changing School Leadership Philosophies to Reverse Childhood Obesity Trends - James M. Lynes III (University of North Florida, 2008)
Childhood obesity is a public health crisis in the United States. By the year 2015 an estimated 24 percent of all children will be obese. Children who are obese miss on average 20 percent more school than their healthy-weight classmates. Additionally, there is a higher risk of developing diabetes and having high blood pressure, and for being overweight as an adult. Childhood obesity is not caused by one factor but is instead caused by a multitude of social factors, the increased consumption of fast foods, video games replacing outdoor activities and unhealthy food options in schools, just to name a few. To create an environment where children learn the benefits of a proper diet and exercise I believe the change must begin in schools. The current model of authoritarian leadership, where decisions are passed from the top down, must be replaced by a democratic and transformational one in which the opinion of the students is sought during the development of health and exercise curricula. By involving the children there will be greater buy-in and they will be more likely to make life-altering decisions to eat and exercise properly. Stakeholders often have better ideas than the leader of how to address problems. To address the obesity problem successfully, stakeholders must be involved.